Genetic association of TNF-α-308 G/A and -863 C/A polymorphisms with late onset Alzheimer′s disease in Azeri Turk population of Iran - Seiied Moitaba Mohaddes Ardebili; Tarlan Yeghaneh; Jalal Gharesouran; Maryam Rezazadeh; Mehdi Farhoudi; Hormoz Ayromlou; Mahnaz Talebi; Morteza Ghojazadeh (Journal of Research in Medical Sciences, 2011)
Background: Recent findings suggest that production of pro-inflammatory cytokines, such as Tumour Necrosis Fac-tor-alpha (TNF-α), is increased in the brain tissue of patients suffering late-onset Alzheimer′s disease (LOAD) and play an important role in the pathogenesis of this disease. Several epidemiological studies also suggest that patients taking anti-inflammatory drugs have a decreased risk of developing AD. TNF-α is an important pro inflammatory cytokine that is unregulated in Alzheimer′s patients. Functional polymorphisms in tumor necrosis factor alpha (TNF-α) can af-fect immune response, inflammation, tissue injury and possibly the susceptibility to Alzheimer disease (AD). Methods: We used the polymorphic DNA markers (-308G/A) and (-863C/A) to study the association of TNF-α gene mutations with Late-onset Alzheimer′s disease (LOAD) and the relation between clinical features and genotypes in af-fected individuals. A total of 160 patient samples and 163 healthy controls from west northern Iran (Eastern Azerbaijan) were genotyped for the two polymorphisms by the PCR-RFLP method and genotype frequencies were statistically de-termined. Results: Our data showed significant difference in TNF-α-308 G/A genotype and pro inflammatory cytokine allele frequencies between the Alzheimer disease patients and healthy subjects. Contrary to that, no significant difference was observed in TNF-α-863 C/A genotype and allele frequencies between these two groups. Conclusions: TNF-α-308 G/A gene polymorphism could affect cerebral inflammatory response and the risk of late-onset Alzheimer disease but -863 C/A polymorphism does not influence the risk of this disease and this possible associa-tion between TNF-α -308G/A and -863C/A gene polymorphisms have to be further elucidated in larger case control studies.